The effect of transient loading on the performance of a mesophilic anaerobic contact reactor at constant feed strength - Senturk, Elif; Ince, Mahir; Engin, Guleda Onkal (ELSEVIER SCIENCE BV, 2013)
Anaerobic contact reactor is a high rate anaerobic process consisting of an agitated reactor and a solids settling tank for recycling. It was proved earlier that this type of reactor design offers highly efficient performance in the conversion of organic matter to biogas. In this study, the effect of transient loading on reactor performance in terms of a number of key intermediates and parameters such as, COD removal, pH and alkalinity change, VFAs, effluent MLSS concentration and biogas efficiency over time was examined. For this purpose, a step increase of organic loading rate from 335 kg COD/m(3) day to 15.61 kg COD/m(3) day was employed. The hydraulic retention time decreased to a value of 8.42 h by an increase in the influent flow-rate during the transient loading. It was observed that the mesophilic anaerobic contact reactor (MACR) was quite resistant to large transient shocks. The reactor recovered back to its baseline performance only in 15 h after the shock loading was stopped. Hence, it can be concluded that this type of reactor design has a high potential in treating food processing wastewaters with varying flow characteristics. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Mesophilic; Anaerobic contact reactor; Shock loading; Recovery; Stability; WASTE-WATER TREATMENT; SEQUENCING BATCH REACTOR; SLUDGE BLANKET REACTOR; FLUIDIZED-BED REACTOR; SHOCK LOADS; MEMBRANE BIOREACTOR; HYDROGEN-PRODUCTION; BIOGAS PRODUCTION; PACKED-BED; DIGESTION; Biotechnology & Applied Microbiology